If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 + 6 = 5x Combine like terms: -14 + 6 = -8 -8 = 5x Solving -8 = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -8 + -5x = 5x + -5x Combine like terms: 5x + -5x = 0 -8 + -5x = 0 Add '8' to each side of the equation. -8 + 8 + -5x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -5x = 0 + 8 -5x = 0 + 8 Combine like terms: 0 + 8 = 8 -5x = 8 Divide each side by '-5'. x = -1.6 Simplifying x = -1.6
| 1=12-z | | Y^2-36=5y | | 5v+14=4v-8 | | 6m-8n=41 | | 1-3x=2x+2 | | 2(b-6)-5(b+3)=15 | | 8m+4n=7 | | -5u+7v=8 | | F(x)=x^4-6x^2-11 | | 130x+204= | | 25h+10=6 | | 4u+4v=-16 | | -5x+3x=-6 | | 4(x+3)=7(4x-11) | | -6x-13=-3x+26 | | 2(x-3)=20x | | 9=x+56 | | -70=-5-5(-2x+2) | | 18-3(w+12)=-45 | | 11x-13=21x-33 | | Y=.75(6.5)+3.3 | | 42+6x=x-38 | | Y=.75(X)+3.3 | | 7x+113=-4x-107 | | 99/100=x/80 | | -4(x+5)=-52 | | 9x+8=14x+23 | | 7x-19=47+10x | | 2cos^2x=1-2sin^2x | | x+45=-8x-63 | | -11+29=-3(x+1) | | -176=3x+4(7x+18) |